The predicament of culture : twentieth-century ethnography, literature, and art - Clifford, James 1945- (Harvard University Press, 1988)
"The Predicament of Culture" is a critical ethnography of the West in its changing relations with other societies. Analyzing cultural practices such as anthropology, travel writing, collecting, and museum displays of tribal art, Clifford shows authoritative accounts of other ways of life to be contingent fictions, now actively contested in postcolonial contexts. His critique raises questions of global significance: Who has the authority to speak for any group's identity and authenticity? What are the essential elements and boundaries of a culture? How do self and "the other" clash in the encounters of ethnography, travel, and modern interethnic relations? In discussions of ethnography, surrealism, museums, and emergent tribal arts, Clifford probes the late-twentieth century predicament of living simultaneously within, between, and after culture.